2020
DOI: 10.3389/fgene.2019.01347
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Heat-Induced circRNAs Related to Lactogenesis in Lactating Sows

Abstract: Heat stress negatively influences milk production and disrupts normal physiological activity of lactating sows, but the precious mechanisms by which hyperthermia adversely affects milk synthesis in sows still remain for further study. Circular RNAs are a novel class of non-coding RNAs with regulatory functions in various physiological and pathological processes. The expression profiles and functions of circRNAs of sows in lactogenesis remain largely unknown. In the present study, long-term heat stress (HS) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Wang et al [29] reported that in cows circCSN1S2 was downregulated during HS condition. Whereas, Sun et al [31] reported circCSN1S1_1 and circCSN1S1_2 which are two circRNAs processed from one host gene, and showed contrasting expression trend during HS condition in sows. This inconsistent expression trend may relate to the exact lactation stage of cows, which need to be considered in further study.…”
Section: Discussionmentioning
confidence: 95%
“…Wang et al [29] reported that in cows circCSN1S2 was downregulated during HS condition. Whereas, Sun et al [31] reported circCSN1S1_1 and circCSN1S1_2 which are two circRNAs processed from one host gene, and showed contrasting expression trend during HS condition in sows. This inconsistent expression trend may relate to the exact lactation stage of cows, which need to be considered in further study.…”
Section: Discussionmentioning
confidence: 95%
“…The miRNA exosome cargo purified from milk samples was sequenced, leading to the identification of 10 miRNAs that were upregulated, and 16 that were downregulated, in the GPS-treated group compared with the control group. These miRNAs were suggested to act as potential regulators of immune functions (136). The expression levels of miR-30a and let-7d were altered by GPS supplementation, again highlighting their essential role in milk.…”
Section: Mirnas and Milkmentioning
confidence: 96%
“…RNA sequencing analysis by Sun et al (2020) revealed heat stress also significantly decreased the levels of casein family genes, CSN1S1, CSN1S2, CSN3 in swine. The analysis of circRNA transcriptomes between non-heat-stressed and heatstressed sows revealed 50 DE circRNAs between the groups.…”
Section: Swine -Meatmentioning
confidence: 96%
“…The authors of a more recent study decided to look into the circRNA profiles in mammary gland of lactating sows under heat stress (Sun et al, 2020), since it was reported that circRNAs are expressed in bovine mammary glands and could regulate milk content (Zhang et al, 2016). Even though swine milk is not a primary product for human consumption, quality and yield of milk in lactating sows plays an important role for feeding viable offspring raised for meat.…”
Section: Swine -Meatmentioning
confidence: 99%